2018
DOI: 10.3390/en11112877
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Microwave Assisted Liquefaction of Lignin in Hydrogen Donor Solvents: Effect of Solvents and Catalysts

Abstract: Lignin, a renewable source of aromatic chemicals in nature, has attracted increasing attention due to its structure and application prospect. Catalytic solvolysis has developed as a promising method for the production of value-added products from lignin. The liquefaction process is closely associated with heating methods, catalysts and solvents. Microwave assisted lignin liquefaction in hydrogen donor solvent with the presence of catalysts has been confirmed to be effective to promote the production of liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Regarding the latter, biomass is currently the world's fourth energy source (about 10-14%) after conventional fossil oil, coal and natural gas. 4,7,8 Therefore, knowing the finite nature of these fossil energy carriers, the International Energy Agency (IEA) estimates that almost half of the energy demand by 2050 should be produced from biomass. 9 Thus, over the past few decades, there has been a tremendous amount of work being done in the area of biomass valorisation to produce valuable products (biochemicals and biomaterials) and energy (biofuels).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the latter, biomass is currently the world's fourth energy source (about 10-14%) after conventional fossil oil, coal and natural gas. 4,7,8 Therefore, knowing the finite nature of these fossil energy carriers, the International Energy Agency (IEA) estimates that almost half of the energy demand by 2050 should be produced from biomass. 9 Thus, over the past few decades, there has been a tremendous amount of work being done in the area of biomass valorisation to produce valuable products (biochemicals and biomaterials) and energy (biofuels).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, approaches to valorize lignin have included microbial-enzymatic, thermochemical (including pyrolysis, hydrothermal, microwave-assisted methods, , etc. ), photochemical, , electrochemical, ,,, and electrochemical photoredox .…”
Section: Demonstrated Electrochemical Routes For Conversion Of Interm...mentioning
confidence: 99%
“…In this context, many works have outlined different thermochemical and biochemical approaches for lignin valorization; , however, just in 2018, a review about lignin ECOD was published by Zirbes and Waldvogel . Therefore, in this section, we will present only the main advances of this field published over the past 5 years as well as some novel methodologies that were not cited in that mentioned review, summarizing key information about these works in Table .…”
Section: Demonstrated Electrochemical Routes For Conversion Of Interm...mentioning
confidence: 99%
“…Microwave heating has the advantages of high heating rate, ease of start-up and shut-down, and low thermal inertia. Therefore, it is widely used in biomass treatment and conversion such as drying, roasting, pyrolysis, gasification and carbonization [1][2][3][4][5]. However, few studies on industrial scale microwave device for biomass conversion were reported [6][7][8].…”
Section: Introductionmentioning
confidence: 99%